Otolith characterization and integrative species identification of adult mesopelagic fishes from the western North Atlantic Ocean - Quigley, Lucinda A.; Caiger, Paul E.; Govindarajan, Annette F.; McMonagle, Helena; Jech, J. Michael; Lavery, Andone C.; Sosik, Heidi M.; Llopiz, Joel K. (Frontiers in Marine Science, 2023)
Fish diversity and ecology in the ocean’s mesopelagic zone are understudied compared to other marine regions despite growing interest in harvesting these potential resources. Otoliths can provide a wealth of taxonomic and life history information about fish, which can help fill these knowledge gaps; however, there has been relatively little research to date on the otoliths of mesopelagic species. Here, a species-specific image library was assembled of sagittal otoliths from 70 mesopelagic fishes belonging to 29 families collected in the western North Atlantic Ocean. Images of adult sagittal otoliths from 12 species were documented and photographed for the first time. The fish were identified to species with a combination of morphological characters and DNA barcoding. Regressions between otolith size and fish length are presented for the six species with the largest sample sizes in this study. This otolith image library, coupled with otolith-length and width to fish-length relationships, can be used for prey identification and back-calculation of fish size, making it a valuable tool for studies relating to food webs in the important yet poorly understood mesopelagic zone. In addition, the 44 fish barcodes generated in this study highlight the benefit of using an integrative taxonomic approach to studies of this nature, as well as add to existing public databases that enable cryptic species and metabarcoding analyses of mesopelagic species.